Choice and determinism: A comment - Bedeian, Arthur G. (Strategic Management Journal, 1990)
This note comments on Lawless and Finch's (1989) empirical test of Hrebiniak and Joyce's (1985) framework of business‐environment relations. In doing so it extends Lawless and Finch's reasoning through the explicit incorporation of an interactionist perspective. A model is presented that amplifies the prevailing organizational adaptation logic by assigning a role to organizational learning and by suggesting how organizations act on environmental information vis‐à‐vis symbolic processes and environmental management strategies.